PENGARUH INFORMASI LABA AKUNTANSI, ALIRAN KAS DAN KOMPONEN ALIRAN KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Ferry, Ferry; Ekawati, Erny (Jurnal Riset Akuntansi dan Keuangan, 2005)
Brfoo 1994, the one way measurcd pdormance of go public compa4y is earning afier tu, but on September 7, 1994 the Indonesian Institute olAccountants (IAI) published the statement of financial Accounting Standard (PSAK) No.2, "statement of Cash Flows" requires companiesto pubtish the statewent of cash flows beginning from January I, tggs. So investors had two kinds measurement of performance go public companies.The objective of study is to aplain the influence of informationcontent of accounting income, total cash Jlows, and components of cash flow with stock price in lidonesian manufacuring firms The accounting income is earning afiir ta,tc before extra ordinary item and discontinued operations and total cash flows is a sum of cash flow from operating activities, cash llow from investing activities, and cash tlow from financing activities.This study was constitute replicated study from Triyono and Yogiyanto (2000) about the association of information content of total cash flows, components of cash Jlows, and accoun:ting income with stock prices or stock returns. This study took sample frorn manufacnring firms lisfed in the Jakarta Stock Exciange @ni) from 1999-iOOZ tnoT"had pubtished aadited financial statement. Stock prices using monthly prices that hadended December 1999-2002. The statistics method used to test ltypotheses is a linier multiple regression. The model was considered: levek')odet.Â  The empirical results with using the first model levels about the influ. hence information of accounting income and total cash flows with stock prices can be explained accounting income gave positive influence and significant with stock prices whereas total cash flows gcMe negative and tlgnil*nt with stock prices. In the second model levels about the influ- ,i"i ,nyn *ation of cash flow from operating actiu.ities, cash flow from investing activities, and cash flow from financing octivities with stock pri, i* b" explained, separated total gash fl9ws into.yomponents. of 'cash flows gave negative influence and significant with stock prices "rp"ifolly iash ltoi from aperating octivities and c-ash flow from finincing activities. In the third model levels obout influence information of acciunting income and components of cash Jlows with stock prices irn be expliined, accounting income gave positive inlluence and significont with stock prices whereas companents of cosh tlows gNe negative influence and significant with stock prices'Keywords : accounting Income, cash Flows, components of cashflows, levels model